Lake Koronia, a wetland in gradual recovery process or a flash from the past? (2023)
Karadimou E., V. Chrysopolitou, S. Katsavouni, V. Navrozidou, D. Papadimos, D. Zervas and V. Tsiaoussi. 2022. Lake Koronia, a wetland in gradual recovery process or a flash from the past? Poster Presentation in 6th European Congress of Conservation Biology: “Biodiversity crisis in a changing world”, Prague, Czech Republic, August 22–26, 2022.